Developing health education to connect subject learning to real life: A pilot study for junior high school students - Nakaoka, Sae; Kawasaki, Hiromi; Yamasaki, Satoko; Mukaishima, Sayo; Sakai, Risako; Li, Yuan; Cui, Zhengai (Journal of family medicine and primary care, 2025)
Family physicians find it difficult to choose correct words when explaining children's symptoms and treatments. The aim of this study is to demonstrate the cross-curricular nature of health education using a case study on its implementation for junior high school students. Through this study, the potential of health education is examined to realize a method that enables students to apply what they learn in school to real-life situations. Family physicians can tailor instructions to junior high school students' learning stages. This theme focused on blood pressure, which varied among junior high school students. A total of 105 junior high school students received health education and provided valid responses. Mean scores in the cognitive domain were 9.3 before, 17.4 immediately after, and 11.6 one year after the education and given. Mean scores in the affective domain were 14.4, 16.3, and 15.0, respectively. Mean psychomotor domain scores were 11.7, 15.7, and 12.8, respectively. The scores increased significantly, indicating the effectiveness of education. Science and mathematics covered several units of health education. Health education intended to be relevant to the subject matter used learning content to explain bodily processes in an easy-to-understand way. The study concludes that health education has value in making explicit links between subject learning and real-life applications. It enables students to gain knowledge and effectively apply subject learning to everyday situations. As family physicians will understand junior high school students' learning and tailoring instructions, they can prompt children to take care of their health.